Plasma cleaning of beryllium coated mirrors. (25th January 2016) - Moser, L; Marot, L; Steiner, R; Newman, M; Widdowson, A; Ivanova, D; Likonen, J; Petersson, P; Pintsuk, G; Rubel, M; Meyer, E; Contributors, JET
Abstract: Cleaning systems of metallic first mirrors are needed in more than 20 optical diagnostic systems from ITER to avoid reflectivity losses. Currently, plasma sputtering is considered as one of the most promising techniques to remove deposits coming from the main wall (mainly beryllium and tungsten). This work presents the results of plasma cleaning of rhodium and molybdenum mirrors exposed in JET-ILW and contaminated with typical tokamak elements (including beryllium and tungsten). Using radio frequency (13.56 MHz) argon or helium plasma, the removal of mixed layers was demonstrated and mirror reflectivity improved towards initial values. The cleaning was evaluated by performing reflectivity measurements, scanning electron microscopy, x-ray photoelectron spectroscopy and ion beam analysis.